Has IFRS improved Accounting Quality in Indonesia? A Systematic Literature Review of 2010-2016 - Wahyuni, Ersa Tri; Puspitasari, Gina; Puspitasari, Evita (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
Research aims: International Financial Reporting Standard or IFRS has been promoted as globally-acceptable accounting standard. Previous studies indicate that in developed countries, in Europe for instance, IFRS implementation demonstrates a positive effect and tendency towards better accounting quality. This research aims to discover the effect of IFRS implementation in Indonesia through studying relevant journal articles published between 2010-2016. The present study provides an overview of how the standard is implemented in the country.Design/Methodology/Approach: Data were collected from 168 research published in the observed period by conducting a structured literature review.Research findings: The results show that research articles on the impact of IFRS in Indonesia is more dominant (53.66%) than that on implementation and issues (23.17%) and the development of IFRS convergence process (23.17%). Out of the 189 frequencies from sampled studies on the impact of IFRS convergence in Indonesia, the study of value relevant (25.39%) and earnings management (24.35%) is the most common method used in discussing the IFRS impact. In general, IFRS convergence has positive impact to the quality improvement of financial statements, as evidenced by the increased relevance of value, the quality of accounting information, the quality of profit, and the company's financial performance as well as the decreasing earnings management practices.Theoretical contribution/Originality: This research contributes to the development of knowledge about IFRS research and the impact of IFRS convergence in a developing country.Practitioner/Policy implication: The results of this study indicate the overall impact of IFRS in Indonesia that can be used as foundation for further research. This study can be used as a reference for future studies, to determine what topics have not been addressed in this study or what topics can be further investigated. Also, regulator can use my findings as a reference, for understanding the benefits of IFRS implementation in Indonesia and for making improvements in their policy and regulations.Research limitation/Implication: Some papers analysed in this paper come from the proceedings of Simposium Nasional Akuntansi (SNA). As proceedings may not be as rigorous as publication in the academic journal, SNA remains as the most prestigious accounting conference in Indonesia which invites high quality papers.